2015
DOI: 10.1007/s13364-015-0224-2
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, proliferation, and cell size in seasonal changes of body and organ weight in male bank voles Myodes glareolus

Abstract: Adult male bank voles undergo the body and organ regression before winter, and in early spring, they resume the growth and reproductive processes. The aim of the present study was to determine whether the seasonal changes of body and organ weight in these animals depend on changes in the number of cells or their size. To study an autumnal regression, wild adult males captured in August were exposed to short photoperiod for 0, 4, and 8 weeks, while to study a spring resumption, overwintered males caught in Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…As studies have shown that increased apoptosis leads to loss of tissue weight (Furuta et al, 1994;Huang et al, 2016;Otsuka et al, 2010), the loss of testis weight in hamsters under SD exposure in this study may be related to the increase in apoptosis levels. This is similar to the findings in white-footed mice, Syrian hamsters, and bank voles, where the levels of testes apoptosis increased and testicular weight decreased under SD conditions (Bonda-Ostaszewska & Wlostowski, 2015;Morales et al, 2007;Young, Zirkin, & Nelson, 2001). In general, the loss of testis weight under SD may be caused…”
Section: Relative Protein Expressionsupporting
confidence: 88%
See 2 more Smart Citations
“…As studies have shown that increased apoptosis leads to loss of tissue weight (Furuta et al, 1994;Huang et al, 2016;Otsuka et al, 2010), the loss of testis weight in hamsters under SD exposure in this study may be related to the increase in apoptosis levels. This is similar to the findings in white-footed mice, Syrian hamsters, and bank voles, where the levels of testes apoptosis increased and testicular weight decreased under SD conditions (Bonda-Ostaszewska & Wlostowski, 2015;Morales et al, 2007;Young, Zirkin, & Nelson, 2001). In general, the loss of testis weight under SD may be caused…”
Section: Relative Protein Expressionsupporting
confidence: 88%
“…Several studies have shown that seasonal rhythm mammals regulate reproductive rhythms via the hypothalamus‐pituitary‐gonadal axis through melatonin secretion by photosensitive organs such as the pineal gland (Kelestimur et al, 2012; Shi, Li, Bo, & Xu, 2013). Current studies on seasonal reproductive rhythms in mammals, such as white‐footed mice ( Peromyscus leucopus ), bank voles ( Myodes glareolus ), Djungarian hamsters ( Phodopus sungorus ), and Syrian hamsters ( Mesocricetus auratus ), have shown that short‐light stimulation induces testicular degeneration, mainly by reducing weight and volume (Bonda‐Ostaszewska & Wlostowski, 2015; Furuta et al, 1994; Martinez‐Hernandez et al, 2018; Young & Nelson, 2001). Testicular atrophy in golden hamsters ( M. auratus ) under short daylight exposure is usually accompanied by decreases in serum luteinizing hormone (LH), follicle‐stimulating hormone (FSH), and testosterone (TTE; Console et al, 2002; Kawazu et al, 2003), whereas long daylight exposure increases serum LH and FSH levels (Turek, Elliott, Alvis, & Menaker, 1975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the correlation coefficients (the “ Results ” section), it may be concluded that the liver and kidney mass appears to be a significant factor affecting oxidative damage; the higher organ mass in reproductive females results in lower oxidative stress as compared to non-reproductive females. Unfortunately, this relationship cannot be easily explained at present; however, assuming that an increase in the organ mass observed in reproductive bank vole females [ 7 , 8 , present study] is associated with changes in cell size rather than their numbers [ 25 ], then the cells of higher size in these females should consume less oxygen and so produce less ROS (due to favorable surface area-to-volume ratio) as compared to non-reproductive females. However, this possible mechanism and an involvement of iron and copper in oxidative stress are not mutually exclusive and need to be studied in detail.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is because hepatocytes engaged in the cell cycle occupy some of the total cells, and other parameters, such as apoptosis and necrosis, may modulate liver weights. (19) These factors reduced the amplitude of proliferation-related increments in the liver/body weight ratios. The thrombocytosis-induced increases in the Ki-67-labeling index and the PCNA-labeling index were eliminated after APS injection, indicating that platelets stimulated liver regeneration independent of TPO.…”
Section: Discussionmentioning
confidence: 99%